Perception of students who enter to study pedagogy of what a good citizen is, public institutions and the effectiveness of political action - Muñoz Labraña, Carlos (2018)
The goal of this report is to study University of Concepcion preservice teachers’ conceptions about what it means to be a good citizen, public institutions, and efficiency of the political action. The study was conducted by using an exploratory and quantitative method. Data about conceptions, attitudes and actions was gathered by using a test developed by the International Association for the Evaluation of Educational Achievement (IEA). In 1999, the test was applied to Chilean students and in 2009; the test was applied to primary and middle school students (Mineduc, 2004). Findings show that pre-service teachers have a low interest as well as comprehension about politics. In addition, they show very low confidence in public institutions such as government, congress, police, justice system, and political parties. On the other hand, they show high value regarding civil rights, the rol of the government and opportunities provided by democracy.